Philippine species of parmotrema (ascomycota,parmeliaceae) - Bawingan Paulina A.; Lardizaval, Mechel P.; Rosuman, Praxedes F.; Fajardo, Weenalai T.; Azuelo, Andrea; Elix, John A.; Hur, Jae-Seoun (2017)
This paper presents a taxonomic treatment of Parmotrema lichens (Ascomycota, Parmeliaceae) collected in the Philippines at high altitudes where they abound, particularly in the mountainous regions of northern Luzon and Mindanao. A total of 30 Parmotrema species were identified: twelve being new records. Results suggest that the Philippines has a potentially rich unknown lichen diversity that remains to be further investigated. Many lichen species are restricted to unexplored forested areas, which in the Philippines are facing alarming degradation; hence, it is extremely important for these habitats to be conserved.